2013
DOI: 10.1039/c3ta11940h
|View full text |Cite
|
Sign up to set email alerts
|

Light metals decorated covalent triazine-based frameworks as a high capacity hydrogen storage medium

Abstract: The structural stability and hydrogen adsorption capacity of an alkali (Li, Na and K) and alkali earth (Mg and Ca) metal atom decorated covalent triazine-based framework (CTF-1) are studied using ab initio density functional calculations. The calculation results revealed that Li, Na, K and Ca atoms can be adsorbed on the CTF-1 with the formation of a uniform and stable coverage due to the charge transfer between the metal atoms and the CTF-1 substrate, thus avoiding the clustering problem that occurs for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…It should be noted that as the number of the decorated Ca atoms increases the distances of Ca atoms to the surface of C 48 B 12 increase while the binding energies of the Ca atoms decrease in the Ca-decorated C 48 B 12 complexes. Similar behavior was reported for Ca-decorated covalent triazine-based frameworks studied by Yu et al 27 It is well known that the aggregation of metal atoms on the surface of materials is a main impediment for efficient hydrogen storage in metal-decorated nanostructures. To check whether Ca atoms tend to aggregate on the C 48 B 12 surface, we carried out more calculations as follows.…”
Section: B the Geometrical And Electronic Structures Of Ca-decoratedsupporting
confidence: 84%
See 1 more Smart Citation
“…It should be noted that as the number of the decorated Ca atoms increases the distances of Ca atoms to the surface of C 48 B 12 increase while the binding energies of the Ca atoms decrease in the Ca-decorated C 48 B 12 complexes. Similar behavior was reported for Ca-decorated covalent triazine-based frameworks studied by Yu et al 27 It is well known that the aggregation of metal atoms on the surface of materials is a main impediment for efficient hydrogen storage in metal-decorated nanostructures. To check whether Ca atoms tend to aggregate on the C 48 B 12 surface, we carried out more calculations as follows.…”
Section: B the Geometrical And Electronic Structures Of Ca-decoratedsupporting
confidence: 84%
“…On the one hand, it is shown that alkali metals or alkaline-earth metals can be used to decrease the aggregation due to their small cohesive energy. [24][25][26][27][28][29][30][31] Theoretical studies showed that Li-and Na-coated fullerenes, where the metal atoms is individually distributed on the fullerenes, can store hydrogen in molecular form with large gravimetric density of 13 wt% and 9.5 wt%. 24,25 Yoon et al explored the hydrogen storage capacity of the light alkaline-earth metal atoms coated C 60 .…”
Section: Introductionmentioning
confidence: 99%
“…48 Grimme's empirical correction scheme for common density functionals has been applied successfully to many chemical problems including molecular hydrogen. 4,[49][50][51][52][53][54] We nd however that Ca loses part of its valence electrons. The resulting Ca ion is more difficult to polarize, hence its van der Waals interaction with molecular hydrogen is probably weakened.…”
Section: -19mentioning
confidence: 83%
“…[9][10][11][12][13][14][15][16][17][18][19][20] CTFs have also been applied as solid base catalysts for the conversion of CO 2 21 and as metal free catalysts for ORR. 22,23 The high surface area and nitrogen amount make CTFs attractive for the storage of gases 6,[24][25][26][27][28] or generally as sorbent materials. [29][30][31] Furthermore, due to the conjugated planar structure, CTFs are organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%